Eroding empire : Western relations with Eastern Europe - Gordon, Lincoln (Washington, D.C. : Brookings Institution, 1987)
This book reviews the attitudes, interests and policies of the major western countries toward Eastern Europe since World War 11.
Includes bibliographical references and index.
oo 22/01/2019
Loans
Keywords: International relations; Foreign relations; Politics and government; Europe, Eastern; Europe; United States